Significant improvement of systemic lupus erythematosus manifestation in children after autologous dendritic cell transfer: a case report and review of literature - Jonny; Terawan Agus Putranto; Yenny Purnama; Roedi Djatmiko; Martina Lily Yana; Enda Cindylosa Sitepu; Raoulian Irfon (SAGE Publishing, 2023)
Dendritic cells (DC) are postulated to play a role in autoimmune diseases such as Systemic Lupus Erythematosus (SLE). We reported a 13-year-old female SLE patient who presents with chronic arthritis accompanied by persistent fever, dyspnea, sleep disturbance, headache, stomatitis, rash, and muscle weakness. The supporting examinations showed abnormal blood cell counts, positive antinuclear antibody profile, serositis, and neuropathy. Immunosuppressants failed to improve the condition. DC-based vaccine derived from autologous peripheral blood which was introduced with SARS-CoV-2 protein was given to this patient. There was a significant improvement in clinical and laboratory findings. Thus, DC immunotherapy appears to be a potential novel therapy for SLE that needs to be studied.